2022
DOI: 10.1155/2022/9165574
|View full text |Cite
|
Sign up to set email alerts
|

Cooccurrence of Talon’s Cusp with Dens Invaginatus in the Maxillary Lateral Incisor: A Case Report with Review of Literature

Abstract: Morphogenic developmental anomalies are common in maxillary lateral incisors, but simultaneous occurrence of two developmental anomalies in a single tooth is relatively uncommon. In this case report, we present a case of cooccurrence of the talon’s cusp with dens invaginatus in the left lateral incisor tooth. Early diagnosis and prompt treatment of such cases are important to prevent any untoward consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There are some reported cases about bilateral talon cusp, 4,5 and bifacial talon cusp 5,6,7 in the literature. Ghosh et al 12 and Colak et al 13 reported talon cusps occurring concurrently with dens invaginatus. Siraci et al 14 reported buccal and palatal talon cusps with pulp extensions on a supernumerary primary tooth.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reported cases about bilateral talon cusp, 4,5 and bifacial talon cusp 5,6,7 in the literature. Ghosh et al 12 and Colak et al 13 reported talon cusps occurring concurrently with dens invaginatus. Siraci et al 14 reported buccal and palatal talon cusps with pulp extensions on a supernumerary primary tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Success of endodontic treatment relies on myriad features of the clinical process, including accurate diagnosis, proper access cavity preparation, biomechanical preparation, obturation and post-endodontic restoration, as well as the physician’s knowledge of root canal anatomy. The majority of maxillary lateral incisors are one-rooted with single canal[ 1 ], but anatomical variations such as the presence of multiple canals[ 2 - 4 ], radicular palatal grooves[ 5 ], dens invaginatus (DI)[ 6 ], talon cusps with DI[ 7 ], enamel projections at cemento-enamel junction, etc [ 8 ] can complicate their endodontic management.…”
Section: Introductionmentioning
confidence: 99%
“…The exact cause of DI formation is unknown, although trauma, genetics, infection of the tooth bud during development, and pressure from adjacent developing tooth germ have been suggested as causes. The clinical appearance of DI varies from normal morphology to conical-, peg- or barrel-shaped, large bucco-lingual dimensions, or association with talon cusp[ 3 , 5 , 7 ]. Based on Oehlers’s classification[ 14 ], according to depth of penetration and communication with the periodontal ligament or periapical tissue (determined radiographically), it is classified into the following three types/four subtypes: type I, an enamel-lined minor invagination that does not extend beyond the cementoenamel junction; type II, an invagination extending apically beyond the cementoenamel junction as a blind sac and which may or may not communicate with the dental pulp but has no communication with the periodontal ligament; type IIIA, an invagination penetrating through the root and laterally communicating with the periodontal space by a pseudo foramen without any direct communication with the pulp; and type IIIB, an invagination penetrating the root to communicate with the periodontal ligament at the apical foramen without any direct communication with the pulp.…”
Section: Introductionmentioning
confidence: 99%